Computer vision-based archery optics - Raj, A. (Augmented Human Research, 2025)
Today, archery is used in sports, hunting, recreational shooting, movies, etc. Traditional sights can lose alignment due to vibration and require tools for zeroing, are time-consuming for adjustment, difficult to see in certain backgrounds, and are affected by parallax. To overcome these challenges, a computer vision-based aiming application for smartphones was developed. The features of this application are digital aiming, zeroing, and arrow drop zeroing without any tools, background-based reticle color inversion, sensor-based incline level indicator, zoom, and zeroed distance autosave. These features aim to improve visibility, ease of adjustment, and aiming without any additional cost. Next, the performance of the sight system was tested by an archer firing arrows at a 50 cm target. A total number of 37 shots were fired outside on 3 days, early morning. By using the new sight, a mean absolute error of 10.85 on day 1, 7.18 on day 2, and 6.25 on day 3 was obtained. The study was limited by a small sample size due to difficulty in finding another skilled archer, as archery is not a common sport and has a huge learning curve. The current study identifies the practicality and efficiency of computer vision-based augmentation, like digital aiming, fast zeroing, and better visibility. Additionally, in future, other studies can work on the use of AI, ML, and sensor-based wind direction prediction in a smartphone application.